PENGARUH PENAMBAHAN POLIOKSIETILEN-(20)-SORBITAN MONOLAURAT PADA KARAKTERISTIK BIOPLASTIK POLI-HIDROKSIALKANOAT (PHA) YANG DIHASILKAN Ralstonia eutropha PADA SUBSTRAT HIDROLISAT PATI SAGU - Khaswar Syamsu, Chilwan Pandji, dan Eva Rosalina Lumbanraja (Department of Agroindustrial Technology, Bogor Agricultural University, 2008)
ABSTRACTPoly-hydroxyalkanoates (PHA) were blended in solution with Polyoxyetilene-(20)-sorbitan monolaurate (Tween20). In presence of Tween20 component, it caused some polymer interaction between PHA and Tween20 component. Shifting of density, tensile strength and elongation at break was observed for PHA/Tween20 blend. Improvement in elongation at break was drastic in case of PHA blend with 5% Tween20. The addition of Tween20 can reduce PHA melting point and degree of crystallinity. The amount of crystalline was lower for PHA/Tween20 blend than PHA without Tween20 component. FTIR analysis proved that the alteration of PHA characteristic was caused by hydrogen bonding between PHA and Tween20 molecules. The highest blending performance based on its flexibility was showed by PHA blend with 5% Tween20.Keywords : Bioplastic, polyhydroxyalkanoates, Ralstonia eutropha, Tween20